Are We Ready for the New Realities in the 21st Century Ivory Tower? - Chaloux, Bruce (Valdosta State University, 2011)
This luncheon address will take a whimsical, yet pointed, look at the changing nature of the academy and how technology, online learning and new student markets are impacting traditional teaching and learning environments. Is the Ivory Tower still standing? What might the Tower of 2021, ten short years from now, look like? Do we need a Tower? Some observations and predictions will be offered...audience reactions required!
Presented at the Online Lifeline Conference, Valdosta State University, Valdosta, Georgia, February 16-18, 2011.
Keywords: Featured Speaker; Education, Higher.; College graduates United States; Distance education